Healthy Relationship Education and Emergency Management Preparedness - Schaller, Nathan (My University, 2025)
This report summarizes my in-person and hybrid field experiences during the period from June 2025 through November 2025, which included two Applied Practice Experiences (APE): one with Claire’s Community, a nonprofit focused on promoting healthy relationship education, and another with the Frontier Field Trip program, a multidisciplinary program that integrates public health and field-based learning. Through these experiences and my coursework, I synthesized and applied five Master of Public Health competencies by designing, implementing, and communicating population-based interventions that engaged diverse audiences and built community partnerships. Through my work with Claire’s Community, I identified key stakeholders—including the Executive Director, local library staff, and community partners—to design and implement community-based interventions that promoted early childhood social-emotional health. I created the Parent/Caregiver Resource Brochure, complementary blog posts, and the storytelling event as accessible tools for caregivers, combining evidence-based strategies with plain language and culturally sensitive designs. By adapting complex health information into both print and digital formats, I strengthened communication across literacy levels and promoted inclusivity. This process also allowed me to advocate for public health and social policies that emphasized caregiver education and child safety while fostering meaningful partnerships that supported community engagement and program sustainability. Similarly, through my Frontier Field Trip experience, I collaborated with program co-directors Drs. Justin Kastner and Jason Ackleson to create an interactive emergency and disaster preparedness program centered on the Cascadia Subduction Zone (CSZ). I designed educational material that presented emergency management concepts and preparedness strategies in an approachable, audience-specific format. By translating technical content into plain language and culturally relevant visuals, I ensured accessibility and encouraged active participation from non-academic audiences. This project further demonstrated my ability to design and deliver public health content tailored to community needs while integrating competencies in health communication, program design, and stakeholder collaboration to enhance public awareness, safety, iv and resilience. A key aspect of working with Dr. Kastner was authoring a “script” that was used to facilitate learning through a hypothetical, futuristic CSZ event. Across both APE experiences and through my diverse coursework, I consistently drew upon and integrated multiple competencies—designing interventions (Competency 9), building coalitions (13), advocating for public health (14), adapting communication for diverse audiences (18), and delivering content effectively (19). Together, these experiences strengthened my ability to synthesize knowledge, engage stakeholders, and apply public health principles in ways that advance health equity, community empowerment, and long-term behavioral change. Competencies for the Food Safety and Biosecurity emphasis area were achieved through coursework and are as follows: • Food safety and biosecurity. • Threats to the food system. • Food safety laws and regulations. • Food safety policy and the global food system. • Multidisciplinary leadership.
Keywords: healthy relationships; emergency preparedness; multidisciplinary; audience-appropriate communication; diverse populations; health literacy